Characterization of essential elements for improved episomal expressions in Kluyveromyces marxianus. Issue 4 (3rd February 2022) - Wu, Pingping; Zhou, Jungang; Yu, Yao; Lu, Hong
Abstract: Kluyveromyces marxianus is a promising cell factory for producing heterologous proteins. Essential components including partition element, copy number control element, promoter, and terminator in multicopy plasmids applicable for K. marxianus are not extensively characterized. The pKD1 is an endogenous multicopy plasmid identified in K. lactis, and the pKD1‐based plasmid is the only multicopy plasmid successfully applied in K. marxianus . The circular plasmid pKD1 contains three major open reading frames, namely A, B, and C . Here, we showed that the A gene was responsible for maintaining the high‐copy number of pKD1‐based plasmid in K. marxianus . Deletion of the B or C gene impaired the stable propagation of pKD1‐based plasmid in K. marxianus, and this defect could not be rescued by the trans expression of B and C genes. In a quantitative analysis of a series of promoters and terminators, AFT1 promoter from Pichia pastoris, OM45 promoter and INU1 terminator from K. marxianus, and a set of synthetic terminators, supported high‐level expressions. A combination of AFT1 or OM45 promoter with INU1 terminator in a pKD1‐based plasmid achieved high‐level expressions of four different heterologous proteins. Our study provides valuable elements for high‐level episomal expressions in K. marxianus . Graphical Abstract and Lay Summary: Essential components of multicopy plasmids in Kluyveromyces marxianus, including partition element, copy number control element, promoter, terminator, have not been extensively characterized. pKD1 was an endogenous multicopy plasmid identified in K. lactis and it contains three major open reading frames, namely A, B, and C . In this study, we showed that the A gene played a major role in controlling the high copy number of pKD1‐based plasmid, while B and C genes were indispensable for the stable propagation of the plasmid in K. marxianus . In the survey of series of promoters and terminators, a combination of AFT1 or OM45 promoter with INU1 terminator in a pKD1‐based plasmid achieved high‐level expressions of four different heterologous proteins. Our study provides valuable elements for high‐level episomal expressions in K. marxianus .